Managerial Training, Capital Participation, and Village Revenue Growth: A Moderated Analysis of Educational Level - Margiyanto Margiyanto; Puji Yanti Fauziah (Education and Sociedad Journal, 2026)
This study examines the influence of village capital investment and managerial training on village-generated revenue, with the educational level of Village-Owned Enterprise directors acting as a moderating variable. A quantitative explanatory design was employed involving 78 active Village-Owned Enterprises in Sleman Regency, Indonesia. Data were collected through questionnaires, financial reports, and official village government documents and analyzed using multiple linear regression and moderation analysis. The results reveal that village capital investment has a positive and significant effect on village-generated revenue, indicating that financial support from village governments strengthens business capacity and expands local economic activities. Managerial training also demonstrates a significant positive influence by enhancing managerial competence, organizational effectiveness, and business innovation. Furthermore, the educational level of Village-Owned Enterprise directors significantly strengthens the effects of both capital investment and managerial training on village-generated revenue. Directors with higher educational attainment are more capable of optimizing resource allocation and applying managerial knowledge to improve organizational performance. The findings suggest that sustainable development of Village-Owned Enterprises requires a combination of adequate financial support, continuous managerial capacity building, and qualified leadership. Strengthening these factors can contribute to improved village economic performance and long-term rural development.